The Efficacy and Safety of Endoscopic Sleeve Gastroplasty as an Alternative to Laparoscopic Sleeve Gastrectomy - Yoon, Jin Young (Clin Endosc, 2021)
Endoscopic sleeve gastroplasty (ESG) is a therapeutic endoscopic technique for reducing the size of the gastric reservoir in obese patients, using a full-thickness endoscopic suturing device. The effectiveness of ESG in weight loss is significantly greater than that of high-intensity diet and lifestyle therapy and lower than that of laparoscopic sleeve gastrectomy (LSG). The efficacy at 12 months after ESG in terms of percentage of total body weight loss and excess body weight loss was approximately 16% and 60%, respectively. The well-known predictive factors for increased weight loss by ESG are good compliance with regular monitoring and post-procedure care involving a multidisciplinary team approach. Although the underlying mechanism of weight loss induced by ESG is debatable, delayed gastric emptying and early satiation are some of the proposed mechanisms. The pooled rate of adverse events after ESG reported in several meta-analysis studies ranged from 1.5% to 2.3% and the incidence of new-onset gastroesophageal reflux disease after ESG was negligible, indicating that ESG has a superior safety profile to LSG. Moreover, ESG reduced the risk of obesity-related metabolic comorbidities, evidenced by the reduction in HbA1c level, systolic blood pressure, triglyceride level, and risk of hepatic steatosis and fibrosis; it even improved the quality of life. ESG could be considered safe and qualify as an alternative treatment to LSG.